ANALISIS KARAKTERISTIK ORGANOLEPTIK IKAN TUNA ASAP YANG DIHASILKAN DENGAN METODE PENGASAPAN TRADISIONAL DI DESA MALALANDA KECAMATAN KULISUSU KABUPATEN BUTON UTARA - Febriana Muchtar; Hastian Hastian (Jurnal Pertanian Khairun, 2023)
Fish smoking is a popular method of fish preservation which extends the shelf life of fish and diversify the range of processed fish products. Smoked tuna is a special dish from Malalanda Village, North Buton Regency that is processed using traditional smoking method using simple equipment. This research was conducted to identify the organoleptic characteristics, referring to the acceptability of a product based on the sensory properties, of smoked tuna produced by local artisans using the traditional smoking method in Malalanda Village, Kulisusu District, North Buton Regency. On-site observation involving randomly-sampled smoked fish artisans was performed. Three tuna fish were obtained from three artisans to undergo organoleptic tests to assess their color, aroma, presentation, and taste. Each sample was assigned a code: Craftsman 1 (T1), Craftsman 2 (T2), and Craftsman 3 (T3). The organoleptic testing involved 37 panelists, consisting of students from the Department of Agricultural Technology at Universitas Sulawesi Tenggara. The ANOVA test revealed that the three types of smoked tuna samples exhibited similar characteristics in terms of color, aroma, presentation, and taste. Specifically, the color characteristics of T1 were rated at 4.27 (liked), T2 at 4.30 (liked), and T3 at 4.30 (liked). The aroma scored T1 = 4.35 (liked), T2 = 4.30 (liked), and T3 = 4.27 (liked), while the presentation showed T1 = 4.30 (liked), T2 = 4.30 (liked), and T3 = 4.27 (liked). Furthermore, the taste was rated T1 = 4.49 (liked), T2 = 4.46 (liked), and T3 = 4.46 (liked). Therefore, no significant differences were found in the organoleptic characteristics of color, aroma, presentation, and taste among the three smoked tuna samples.Keywords:Smoked tuna, organoleptic characteristics, traditional fish smoking process